PENERAPAN GOAL SETTING UNTUK MENINGKATKAN SELF REGULATION LEARNING PADA SISWA SMK: PENDEKATAN EKSPERIMEN NON-RANDOMIZED CONTROL TRIAL - Silmida Faujiah; Widyastuti Widyastuti; Ghozali Rusyid Affandi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Self-regulation learning is important for students because it consists of thoughts, feelings, and behaviors that are generated and monitored by themselves to achieve goals. Self regulation learning can grow with the determination of learning goals that can direct individuals to focus on achieving the desired learning targets. One of the factors that can improve self-regulation learning is goal setting because it is a planning process to achieve learning goals. This quasi-experimental study aims to obtain information on the application of goal setting in improving self-regulation learning. The subjects in this study were 82 students who were divided into 2 groups, namely 41 treat groups and 41 control groups. Using the research type of non-randomized control trial method with pretest and post-test control group design. The data collection technique used the Self regulation learning adaptation scale with a reliability of 0.927. The collected data were analyzed using the independent samples t-test and paired samples t-test analysis tests. It was found that the application of goal setting had an impact on students' self regulation learning. It is known that the results of the treat group are higher than the results of the control group.